The effect of job promotion and work environment on job satisfaction with work motivation as a moderating variable : case study of lecturers Politeknik ATI Padang - Indah Arisaq; Harif Amali Rivai; Hendra Lukito (Institute of Computer Science (IOCS), 2023)
This study aims to obtain empirical evidence regarding the effect of job promotion and work environment on job satisfaction with work motivation as a moderating variable. This research was conducted at Politeknik ATI Padang. The sampling technique is the saturated sample method, so the population of respondents used is all permanent lecturers at the Politeknik ATI Padang of 65 lecturers. The analytical method used is descriptive statistical analysis using SmartPLS 3.0. Based on the results of research testing shows that job promotion has a positive and significant effect on job satisfaction; work environment has a positive and significant effect on job satisfaction; work motivation has a positive and significant effect on employee performance ; job promotion has no on job satisfaction with work motivation as a moderating variable; work environment has a positive and significant effect on job satisfaction with work motivation as a moderating variable. Based on the results R square value was 0.642, means that 64.2% of the job satisfaction of lecturers at the Politeknik ATI Padang is explained by the variables of promotion, work environment and work motivation. While the remaining 35.8% is influenced by other variables not explained in this study.